Deformation-induced structure evolution of poly(butylene terephthalate)/poly(carbonate) blends during uniaxial stretching. Issue 45 (7th November 2017) - Zhang, Wenyang; Li, Jingqing; Shang, Yingrui; Li, Hongfei; Jiang, Shichun; An, Lijia
Abstract : Phase separation occurs during deformation for all the PBT/PC samples. At large strains, microfibril slippage plays a leading role in the macroscopic strain. Abstract : The crystalline structure evolution of poly(butylene terephthalate)/poly(carbonate) (PBT/PC) during stretching was investigated by in situ synchrotron wide-angle X-ray scattering (WAXS) and small-angle X-ray scattering (SAXS) at 70 °C. The WAXS results demonstrated that the crystallinity and crystallite size ( D 100 ) decrease with deformation. The α–β transition was observed during the deformation of PBT/PC blends. The orientation degree of the PBT (100) diffraction increases with strain in the PBT/PC blends. The SAXS data showed that PC is located in the interlamellar region of PBT for the undeformed samples. A structure model was proposed to describe the stretching-induced structure evolution of the PBT/PC blends.